Did limits on payments for tobacco placements in US movies affect how movies are made?. Issue 1 (28th January 2016) - Morgenstern, Matthis; Stoolmiller, Mike; Bergamini, Elaina; Sargent, James D
Abstract : Objective: To compare how smoking was depicted in Hollywood movies before and after an intervention limiting paid product placement for cigarette brands. Design: Correlational analysis. Setting/Participants: Top box office hits released in the USA primarily between 1988 and 2011 (n=2134). Intervention: The Master Settlement Agreement (MSA), implemented in 1998. Main outcome measures: This study analyses trends for whether or not movies depicted smoking, and among movies with smoking, counts for character smoking scenes and average smoking scene duration. Results: There was no detectable trend for any measure prior to the MSA. In 1999, 79% of movies contained smoking, and movies with smoking contained 8 scenes of character smoking, with the average duration of a character smoking scene being 81 s. After the MSA, there were significant negative post-MSA changes (p<0.05) for linear trends in proportion of movies with any smoking (which declined to 41% by 2011) and, in movies with smoking, counts of character smoking scenes (which declined to 4 by 2011). Between 1999 and 2000, there was an immediate and dramatic drop in average length of a character smoking scene, which decreased to 19 s, and remained there for the duration of the study. The probability that the drop of −62.5 (95% CI −55.1 to −70.0) seconds was due to chance was p<10 −16 . Conclusions: This study's correlational data suggest that restricting payments for tobacco product placement coincided with profound changes in the duration of smoking depictions in movies.